1990
DOI: 10.1164/ajrccm/142.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Value of ELISA Using A60 Antigen in the Diagnosis of Active Pulmonary Tuberculosis

Abstract: This investigation was undertaken to assess the effectiveness of an enzyme-linked immunosorbent assay (ELISA) using A60 antigen in ascertaining diagnosis in hospitalized patients suspected to have pulmonary tuberculosis (TB) but with negative sputum stains. Cultures were performed to confirm active or inactive disease. IgG and IgM antibody activity was determined by adding a 1:100 dilution of serum to plates coated with A60 antigen. After addition of peroxidase-conjugated antihuman IgG or IgM and color develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 6 publications
6
31
1
Order By: Relevance
“…9 These findings are more or less in the agreement with earlier reports. [10][11][12] In this study, specificity of the tests ranged from 66.6% to 80% in non-tuberculosis pulmonary pathology, but some patients analyzed departed strikingly from this norm and yielded different patterns of sero-positivity. Other authors have also reported similar events.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…9 These findings are more or less in the agreement with earlier reports. [10][11][12] In this study, specificity of the tests ranged from 66.6% to 80% in non-tuberculosis pulmonary pathology, but some patients analyzed departed strikingly from this norm and yielded different patterns of sero-positivity. Other authors have also reported similar events.…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, relatively low seropositivity was seen in cases of sputum negative active pulmonary tuberculosis compared to those of sputum positive active pulmonary tuberculosis as shown in a previous study. 11 As far as serology in patients with extra pulmonary tuberculosis is concerned, a sensitivity of 47.3% for IgG was observed. The mean antibody levels were lower than the active pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gupta et alshowed sensitivity of 98.3% and specificity of 90% of combined IgG and IgA test using antigen A60 in adult pulmonary tuberculosis cases (5). AI Hajjaj et alshowed sensitivity of 87% and specificity of 95% for combined IgG and IgM estimation using A60 antigen (6), while Charpin et al showed sensitivity of 68% for combined lgG and IgM estimation (7). The wide variations in sen.sitivity of different combination of antibody types could be due to the different geographical areas, different antigen used, as well as severity of disease in different studies.…”
Section: Resultsmentioning
confidence: 99%
“…The A60 antigen, which is a thermostable component of the purified protein derivative, has been used in the serodiagnosis of tuberculosis. In patients with smear-negative but culture-positive pulmonary tuberculosis, measurement of both IgM and IgG by ELISA revealed a sensitivity of 68% and a specificity of 100% (11). In the pediatric group, at a chosen specificity of 98%, anti-A60 IgG antibodies were observed in 68% of children with clinically active tuberculosis (15).…”
Section: Discussionmentioning
confidence: 98%